The role of growth differentiation factor 11 on macrophage polarization and its implications in hepatocellular carcinoma; El papel del factor de crecimiento y diferenciación 11 en la polarización de macrófagos y su implicación en el carcinoma hepatocelular - Escobedo Calvario, Óscar Alejandro (Universidad Autónoma Metropolitana, 2020)
The growth differentiation factor 11 (GDF11) promotes the loss of an aggressive phenotype in various tumors, which has been studied in our research group using cell lines derived from hepatocellular carcinoma (HCC). Due to this loss in aggressiveness directly in transformed cells, in the present work, we focus on the study of the tumor microenvironment (TME), specifically macrophages with immunosuppressive and antiinflammatory characteristics (M2) from which the tumor obtains advantages such as proliferation, invasion, and cell migration. For this, macrophages derived from the THP1 cell line differentiated with PMA (200 ng / mL) were cultured, which responded to the activation mediated by GDF11 (50 ng / mL) observing phosphorylation of the Smad2 / 3 proteins at 5 minutes. , indicating that these cells respond to signaling mediated by this molecule and that it may also be involved in polarity. Furthermore, it was found that GDF11 ligand does not alter cell viability or proliferation. Macrophage activation was analyzed using LPS (50 ng/mL) and anti-inflammatory interleukins (IL-4/13) observing the acquisition of their M1 and M2 polarity, respectively, by flow cytometry. On the other hand, different polarization methods were carried out by using conditioned media (CM) derived from HCC cell lines in which macrophages obtain a more efficient M2 polarization, observed with the presence of the CD206 marker. Once the M2 polarity was standardized, the macrophages were treated with GDF11 in competition with IL-4/13, observing that GDF11 induces a decrease in the percentage of CD206 + cells, indicating that this molecule is involved in re-polarization and that it also suggests a reduction in aggressiveness in liver tumors. On the other hand, it was observed that GDF11 is involved in lipid metabolism, since a decrease in total cholesterol levels was detected, verifying this same result with the use of statins, mainly atorvastatin (10 µM). The results indicate that GDF11 indirectly modulates the mevalonate pathway and cholesterol synthesis, affecting the polarity of M2 macrophages, suggesting that the tumor microenvironment (TME) is also affected and that it may have repercussions, reducing the aggressiveness of the tumor.; El carcinoma hepatocelular (HCC) representa un serio problema a nivel mundial, abarcando mas del 80% de los tumores primarios, donde se estima que representa el cuarto lugar en mortalidad. El HCC tiene diferentes etiologías incluyendo infecciones virales como la hepatitis B y C, xenobióticos, alto consumo de alcohol y de lípidos como el colesterol. El colesterol promueve la formación de tumores con una elevada agresividad, grandes y altamente vascularizados. El colesterol puede ser obtenido de la dieta o mediante el incremento de la síntesis de novo por la ruta del mevalonato promovido por la enzima limitante HMG-CoA reductasa. En el proceso del desarrollo tumoral ocurre una inflamación crónica, también llamada inflamación no resuelta, la cual promueve el reclutamiento de leucocitos, que forman parte del microambiente tumoral (TME). Estas células del sistema inmunológico forman un tipo específico de TME llamado como microambiente inmunológico tumoral (TIME). Dentro del TIME las células que mas abundan son los macrófagos, y que también son llamados macrófagos asociados a tumores (TAM) con una activación o polaridad alternativa (M2) con respuesta pro-tumoral, es decir, le brindan agresividad al tumor. Los TAM son sometidos a un ambiente anti-inflamatorio y ejercen la inmunosupresión de otros leucocitos. Moléculas como el TGF-β son secretadas por el tumor promoviendo una regulacion autocrina y/o paracrina activando M2-TAM, los cuales son identificados mediante marcadores especificos como lo son CD163 y CD206. El uso de moléculas que puedan revertir la polaridad de los TAM y que además ataquen a las células transformadas representaría una nueva estrategia para el tratamiento de diversos tumores, incluyendo el HCC. Se ha estudiado el papel del factor de crecimiento y diferenciación 11 en células derivadas de HCC donde disminuye su efecto de agresividad ya mencionados y que además tiende a realizar los efectos opuestos al TGF-β, como la disminución en la síntesis de colesterol y la migración celular. Por lo que se propone a esta molécula como una molécula capaz de activar macrófagos con una respuesta anti-tumoral (M1). Cabe mencionar que el uso de estatinas también promueven la disminución del colesterol mediante la inhibición de la enzima limitante HMG-CoA reductasa y promoviendo la polarización de macrófagos en diferentes modelos experimentales. El uso de ambas moléculas representaría una terapia combinada con una elevada respuesta.